2012
DOI: 10.5152/balkanmedj.2011.012
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Nerve Stimulator and Ultrasonography Application for Brachial Plexus Anesthesia

Abstract: Objective: Axillary brachial plexus block can be achieved through various techniques in upper extremity operations. The purpose of our study was to compare the efficacy of axillary brachial plexus block using an ultrasound technique with peripheral nerve stimulation technique. Material and Methods:Sixty patients for whom elective forearm and hand surgery was planned were included in the study. Group 1 (n=30) was given an axillary block by using ultrasonography, Group 2 (n=30) was given axillary block by using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In most studies, the success rate of US-guided BPB has been reported to be 95% (24,25) and 100% (26), while, in studies comparing the US and NS techniques, the rates were 85% (27) and 90% (28).…”
Section: Discussionmentioning
confidence: 99%
“…In most studies, the success rate of US-guided BPB has been reported to be 95% (24,25) and 100% (26), while, in studies comparing the US and NS techniques, the rates were 85% (27) and 90% (28).…”
Section: Discussionmentioning
confidence: 99%